MATLAB computational routines for moment-curvature relation of reinforced concrete cross sections - Melo,Gabriel Figueiredo de (2021)
ABSTRACT: In this paper we present a set of MATLAB routines for evaluation of the moment-curvature relationship of reinforced concrete cross sections. This is a topic of major importance for both academic and practical design purposes in the context of structural engineering. The computational routines were developed to be simple, general and flexible. This allows wide practical application and future improvements and modifications. The well-known fibers approach is employed, but an alternative development of the method is also presented. This is interesting from the conceptual point of view. Finally, numerical comparisons are presented to validate the routines.